Life in the era of pandemic: a fiqhī framework - Muhsin, Sayyed Mohamed (Mission Soft Foundation, 2021)
Covid-19 is still around us but with more furious nature despite the strict use of various methods and efforts to combat it, only to know that it is more powerful. How life should be in this era of the pandemic? How should we wisely plan our lives and future? Are there any principles or maxims in Islamic jurisprudence that help us decide our action and inaction? How to balance our faith, health and wealth? These are some common questions that float in our minds for the last many days.